2023
DOI: 10.1177/0310057x231196915
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of anaesthesia incidents during caesarean section reported to webAIRS between 2009 and 2022

Victoria A Eley,
Martin D Culwick,
Alicia T Dennis

Abstract: Anaesthesia for caesarean section occurs commonly and places specific demands on anaesthetists. We analysed 469 narratives concerning anaesthesia for caesarean section, entered by Australian and New Zealand anaesthetists into the webAIRS incident reporting system between 2009 and 2022. As expected, compared with the remaining 8978 database entries, the 469 incidents were more likely to be emergency cases (relative risk (RR) 1.95), more likely to occur between 18:00 and 22:00 hours (RR 1.81) and between 22:00 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…For patients experiencing signi cant vaginal bleeding, prompt surgical haemostasis is necessary. Such emergency surgeries, conducted without su cient preoperative preparation, heighten the risk of anaesthetic complications [23] and increase the likelihood of further complications such as infections [24] and organ damage. Patients often endure signi cant pain and suffering from suboptimal experiences during these emergency procedures, causing both physical and psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…For patients experiencing signi cant vaginal bleeding, prompt surgical haemostasis is necessary. Such emergency surgeries, conducted without su cient preoperative preparation, heighten the risk of anaesthetic complications [23] and increase the likelihood of further complications such as infections [24] and organ damage. Patients often endure signi cant pain and suffering from suboptimal experiences during these emergency procedures, causing both physical and psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Eley et al report on 469 caesarean-related incidents reported to webAIRS between its inception in 2009 and early 2022. 2 Bright et al report on 684 adult cardiac arrests over a similar period. 3 Mistry and Endlich, drawing from the first 8000 webAIRS reports again over a similar period, discuss 26 incidents related to paediatric regional anaesthesia.…”
mentioning
confidence: 99%